N-methyl-D-aspartate receptor antagonists reduce synaptic excitation in the hippocampus - Hablitz, JJ (J Neurosci, 1986)
The hypothesis that synaptic excitation in the CA1 region of the hippocampus is mediated in part by N-methyl-D-aspartate (NMDA) receptors was tested using intra- and extracellular recording techniques. Synaptic potentials elicited by stratum radiatum stimulation were examined in individual neurons before and after bath application of the NMDA receptor antagonist, DL-2-amino-5- phosphonovalerate (APV). This antagonist reduced both excitatory and inhibitory postsynaptic potentials (EPSPs and IPSPs). When IPSPs were suppressed by the addition of picrotoxin, EPSPs were seen in isolation. APV reduced these EPSPs but did not block synaptic transmission. This antagonist demonstrated anticonvulsant actions when tested against picrotoxin-induced epileptiform activity. These results suggest that, as in the spinal cord and neocortex, synaptic excitation in the CA1 region of the hippocampus is partially mediated by APV-sensitive NMDA receptors. The fact that synaptic activity is not blocked by NMDA antagonists indicates that EPSPs in CA1 neurons are not mediated solely by this receptor.